Enhanced Fatty Acid Synthesis Leads to Subset Imbalance and IFN-γ Overproduction in T Helper 1 Cells - Iwata, Shigeru; Zhang, Mingzeng; Hao, He; Trimova, Gulzhan; Hajime, Maiko; Miyazaki, Yusuke; Ohkubo, Naoaki; Satoh Kanda, Yurie; Todoroki, Yasuyuki; Miyata, Hiroko; Ueno, Masanobu; Nagayasu, Atsushi; et al. (Frontiers in Immunology, 2020)
Recent reports have shown the importance of IFN-γ and T-bet+ B cells in the pathology of SLE, suggesting the involvement of IFN-γ-producing T-bet+ CD4+ cells, i.e., Th1 cells. This study determined the changes in Th1 subsets with metabolic shift and their potential as therapeutic targets in SLE. Compared with healthy donors, patients with SLE had higher numbers of T-bethiCXCR3lo effector cells and T-bet+Foxp3lo non-suppressive cells, which excessively produce IFN-γ, and lower number of non-IFN-γ-producing T-bet+Foxp3hi activated-Treg cells. These changes were considered to be involved in treatment resistance. The differentiation mechanism of Th1 subsets was investigated in vitro using memory CD4+ cells obtained from healthy donors and patients with SLE. In memory CD4+ cells of healthy donors, both rapamycin and 2-deoxy-D-glucose (2DG) suppressed T-bet+Foxp3- cells, and induced T-bet+Foxp3+(lo/hi) cells. Rapamycin induced IFN-γ-producing T-bet+Foxp3lo cells accompanied with enhanced lipid metabolism, whereas 2DG induced IFN-γ-non-producing T-bet+Foxp3hi cells. In memory CD4+ cells of SLE patients, inhibition of fatty acid synthesis, but not β-oxidation, suppressed IFN-γ production, and up-regulated of Foxp3 expression in T-bet+Foxp3+ cells. Metabolic regulators such as fatty acid synthesis inhibitors may improve the pathological status by correcting Th1 subset imbalance and overproduction of IFN-γ in SLE.